Polysaccharides, Next Potential Agent for the Treatment of Epilepsy? - Xie, Xuemin; Wu, Youliang; Xie, Haitao; Wang, Haiyan; Zhang, Xiaojing; Yu, Jiabin; Zhu, Shaofang; Zhao, Jing; Sui, Lisen; Li, Shaoping (Frontiers in Pharmacology, 2022)
Epilepsy is a chronic neurological disorder. Current pharmacological therapies for epilepsy have limited efficacy that result in refractory epilepsy (RE). Owing to the limitations of conventional therapies, it is needed to develop new anti-epileptic drugs. The beneficial effects of polysaccharides from Chinese medicines, such as Lycium barbarum polysaccharides (COP) and Ganoderma lucidum polysaccharides (GLP), for treatment of epilepsy include regulation of inflammatory factors, neurotransmitters, ion channels, and antioxidant reactions. Especially, polysaccharides could be digested by intestinal microbial flora, referred as “intestinal brain organ” or “adult’s second brain”, may be the target for treatment of epilepsy. Actually, polysaccharides can effectively improve the type and quantity of intestinal flora such as bifidobacteria and lactic acid bacteria and achieve the purpose of treating epilepsy. Therefore, polysaccharides are hypothesized and discussed as potential agent for treatment of epilepsy.